Deskripsi Karakter Jujur pada Siswa Madrasah Tsanawiyah Negeri Kota Jambi - Riko Firmansyah; Yunita Siregar (Dirasat: Jurnal Manajemen dan Pendidikan Islam, 2019)
This study aims to describe the character of the students, especially the honesty character of the eighth grade students of MTsN 1 Jambi City. The approach used in this research is a quantitative approach. While the type of research used is the type of survey research with a questionnaire research instrument. The subjects of this study were students of class VIII E and VIII F MTsN 1 Jambi City, with a total of 25 respondents. The data analysis technique used is descriptive statistical analysis techniques. While the results of the study show that the questionnaire character of honesty of students is classified in the category of “very good.” In class VIII E, there were 16.7% of statements that were answered well by students, and there were 83.3% of statements that were answered very well by students. Whereas in class VIII E, there were 25.9% of statements that were answered well by students, and there were 74.1% of statements that were answered very well by students. Based on the results of the questionnaire, it can be concluded that the students of MTsN 1 Jambi City, especially class VIII E and VIII F, have had a very good attitude in honesty.